Pengaruh Electronic Word of Mouth Characteristics pada Repurchase Intention melalui Trust dan Perceived Usefulness sebagai mediasi pada Aplikasi Sociolla. - Grestanty Christie Kadang; Margaretha Pink Berlianto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
The purpose of this study is to examines perception of three characteristic of electronic word-of-mouth (EWOM) which quantity, credibility, and quality to customer’s online repurchase intention mediated by trust and perceived usefulness on Sociolla application. A total of 228 respondents who had previously made an online purchase from Sociolla. Results show that three EWOM characteristic has negative direct effect on online repurchase intention. Trust mediates the quantity and quality EWOM characteristic on online repurchase intention, while credibility has negative influence. Perceived usefulness mediates the quantity and quality EWOM characteristic on online repurchase intention, while credibility has negative influence.